Suitable Layout of Semi-transparent Solar Cells for Planting Strawberries in Greenhouses - Vongpanya, Tadam; Mongkon, Sulaksana; Polvongsri, Sarawut (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2023)
This research investigated the most suitable arrangement of semi-transparent solar cells for strawberries planting in greenhouses. The study was divided into two parts. The first part was to evaluate the electrical performance and the amount of Photosynthetic Photon Flux Density (PPFD) that strawberry required for photosynthesis. In this case, 4.72 watts per cell of polycrystalline solar cell was used to arrange in 3 patterns: spacing type 1, spacing type 2, and chessboard type and a 2 m2 of semi-transparent solar panel was created. The study revealed that the spacing type 2 and checkerboard type obtained PPFD of 755.47 and 751.17 μmol/m2/s, respectively, which were suitable for strawberry planting. The solar panel performance was tested to develop empirical equations for predicting the power production from both patterns. In the second part, the equations obtained from the first part of the study were used to simulate energy production in the case of installing on a Lean-to strawberry greenhouse roof with a width of 6 m, a length of 12 m and a height of 4.95 m. It was found that the spacing type 2 model of semi-transparent solar panel could produce 7,309.58 kWh of electrical energy, equivalent to 32,893.11 Baht/year of electricity charge from the investment of 197,500 Baht and a payback period of 6.00 years. On the other hand, the chessboard of semi-transparent solar panel was able to produce 7,477.09 kWh/year of electrical energy, equivalent to 33,646.91 Baht/year with the same investment of 197,500 Baht and a payback period of 5.87 years.